KAJIAN YURIDIS ATAS PENGADAAN TANAH IBU KOTA NUSANTARA TERKAIT OBJEK TANAH ULAYAT MASYARAKAT ADAT DI PENAJAM PASER UTARA: Juridical Study Of Land Acquisition Nusantara Capital City Related To Indigenous People Customary Land In Penajam Paser Utara - Hanna Putri Avrillia Tinambunan; Hasni (Faculty of Law, Universitas Trisakti, 2024)
The Government of Indonesia is currently undertaking the Nusantara Capital City project, which requires land acquisition for the construction of the new capital. This legal research aims to explore the proper procedures for land acquisition in the context of the Nusantara Capital City project, the legal protection for the indigenous communities of Penajam Paser Utara whose land is being used for the project, and the challenges encountered during the land acquisition process. The research employs a normative legal research method. The findings indicate that the land acquisition carried out by the government, specifically by the Nusantara Capital City Authority, complies with the requirements set by the applicable laws and regulations. However, despite this compliance, the legal protection for affected communities remains insufficient, and several challenges have been identified in the implementation of the land acquisition process. The conclusion is that while the procedures align with legal requirements, there is still a need for improved legal protection and resolution of the challenges faced during the land acquisition for the Nusantara Capital City project